Personnel Management (Staffing) in Managing the Learning Process at the Bina Cipta Ujungberung Community Learning Activity Center (PKBM) - Okke Rosmaladewi; Riani Juniarti; Risa Rosyadah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This research is motivated by the problem of one of the management functions, both in preparing institutional personnel starting from recruiting workers, developing them to the business and strategy being carried out. The purpose of this study was to obtain information about staffing management at PKBM Bina Cipta Ujung Berung starting from planning, implementing, and evaluating voluntarily and involving a lot of closeness between family members with honorariums that are not sufficient in standard but still doable. running in accordance with the duties and functions of each PKBM member, so that each workforce provides maximum efficiency for the organization. This research method is to conduct a survey and collect data relevant to the topics discussed to obtain information related to personnel management at PKBM Bina Cipta Ujungberung. With proper staffing management can determine the success of a PKBM institution.